2012
DOI: 10.1177/0748233712436645
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticide residues in biological compartments of healthy mothers

Abstract: The present study was conducted to detect placental and breast milk (BM) transfer of organochlorine pesticides (OCPs) between biological compartments in healthy lactating mothers. The study explores the effect of parity, breast-feeding and urban/rural residence on body burden of OCP residues. The study included 38 healthy participants submitted to cesarean delivery. Sociodemographic data and specimens of maternal and umbilical sera, adipose tissue (Adp T) and BM were collected. Specimens were analyzed to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
0
15
0
2
Order By: Relevance
“…Mean residues of DDE detected in the three groups examined were 41 ± 5.2, 48 ± 6.2 and 31 ± 2.5 n g/g for breast cancer cases, benign breast disease cases and controls, respectively, indicating significantly lower residues in blood serum from control females (Table 3). In addition, Elserougy et al [31] found a high odds ratio (8.3) in o,p’ -DDD between maternal and umbilical sera of mothers, suggesting potential placental transfer of OCPs between mothers and their children during pregnancy.…”
Section: Detection Of Ocp Residues In Human Serum In African Countriesmentioning
confidence: 99%
“…Mean residues of DDE detected in the three groups examined were 41 ± 5.2, 48 ± 6.2 and 31 ± 2.5 n g/g for breast cancer cases, benign breast disease cases and controls, respectively, indicating significantly lower residues in blood serum from control females (Table 3). In addition, Elserougy et al [31] found a high odds ratio (8.3) in o,p’ -DDD between maternal and umbilical sera of mothers, suggesting potential placental transfer of OCPs between mothers and their children during pregnancy.…”
Section: Detection Of Ocp Residues In Human Serum In African Countriesmentioning
confidence: 99%
“…Those POPs are associated with human health problems such as cancer. The study done by [40] reported that mothers who are exposed to lindane, can accumulate it into breast milk, o, p-dichlorodiphenyldichloroethane (DDD) can accumulate in maternal serum and total dichlorodiphenyltrichloroethane (DDT) can accumulate in the umbilical serum [40]. This reflects their potential placental and breast milk transfer to her child during pregnancy and lactation [40].…”
Section: Chemical Pesticidesmentioning
confidence: 99%
“…Also, according to the Stockholm Convention, among the 12 Persistence Organic Pollutants (POPs), nine are pesticides including aldrin, chlordane, dichlorodiphenyltrichloroethane (DDT), dieldrin, endrin, heptachlor, hexachlorobenzene (HCB), mirex and toxaphene [40]. Those POPs are associated with human health problems such as cancer.…”
Section: Chemical Pesticidesmentioning
confidence: 99%
See 2 more Smart Citations